MENINGKATKAN KETERAMPILAN MENULIS DIALOG PADA MATA PELAJARAN BAHASA INDONESIA MELALUI PENDEKATAN COOPERATIVE LEARNING SISTEM STAD PADA SISWA KELAS III MI PULOERANG LAKBOK KABUPATEN CIAMIS - Yuyun Yuningsih; Dodo (Yayasan Insanulhaq, 2023)
One of the problems faced by the teacher is the passivity of students in class, in group study in class to express opinions, it can be said that the students' abilities are not yet fluent. not optimal, Indonesian learning achievement is still low, especially in formative tests, summative students are not yet brave enough to answer questions or express opinions, the use of models or approaches in learning is not maximized. The research model is a procedure that describes how this research is carried out. In this class action research, the researcher used the action research model developed by Kemmis and McTaggart (1990:11). Based on the success indicator, namely 75% of the class population scored above the KKM, the action in cycle II was successful. As many as 16 students (88.89%) scored above the KKM. The learning process is further improved, namely students have done peer tutoring and students are more active in learning activities with the teacher. Giving material that has been repeated makes students understand more about the material presented by the teacher. Students who better understand the meaning of the activities carried out by the teacher help friends who do not understand. Thus cooperative learning is achieved. In the pre-action, the dialogue writing skills of class III MI Puloerang Lakbok students were still low. Students who can achieve KKM only 3 children (16.67%). After carrying out the STAD type cooperative learning actions in the first cycle, it produced 8 students (44.44%). Furthermore, in cycle II, there were 16 students (88.89%) who succeeded in achieving the KKM. BIBLIOGRAPHY Anita Lie. 2002. Cooperative Learning. Jakarta: Gramedia. Dimyati dan Mudjiono.2009. Belajar dan pembelajaran, Jakarta Rineka Cipta Haryadi dan Zamzani. 1996/ 1997. Peningkatan Keterampilan Berbahasa Indonesia, Jakarta. DepDikBud Dirjen Dikti PPTK Isjoni. 2009. Cooperative Learning. Bandung : Alfabeta Kemmis, San Mc. Taggart, R.1990. The Action Reseach Planner. Deakin University Larry King Bill GILBERT. 2007 Seni berbicara, Jakarta : PT Gramedia Pustaka Utama Slamet, 2008. Keterampilan-Keterampilan Berbahasa Indonesia. Surakarta: UNS Press. Suharjono, 1995. Pedoman Karya Tulis Ilmiah, Jakarta : Dep. P & K Suharjono. 2007. PTK sebagai Kegiatan Pengembangan Profesi Guru, Jakarta : Bumi Aksara Suharsimi Arikunto. 2006 Penelitian Tindakan Kelas, Jakarta : PT Bumi Aksara. UU RI No. 20 tahun 2003 tentang SISDIKNAS. Bandung : Fokus Media UU RI No 14 tahun 2005 tentang guru dan dosen. Jakarta : Novindo Pustaka Mandiri